Chairman of the Board : A Biography of Carl A. Gerstacker - Brandt, E. N. (Book collections on Project MUSE., 2003)
Carl A. Gerstacker was born in 1916 in Cleveland, Ohio. At an early age his father, Rollin, instilled in him an interest in finance and the stock market. In 1930, when Carl turned fourteen, Rollin advised his son to withdraw his paper-route and odd-job money from a local bank and invest it all in The Dow Chemical Company. It was the beginning of a relationship that would last a lifetime. After high school, Carl landed an hourly position with Dow Chemical as a lab assistant and, at the same time, pursued an engineering degree at the University of Michigan as part of the compan.